Gender Differences in Head and Neck Posture Among Smartphone Users While Walking: Insights from Field Observations in Taipei - Yi-Lang Chen; Ting-Hsuan Wang; Wei-An Chang; Hong-Tam Nguyen (Journal of Functional Morphology and Kinesiology)
Background/Objectives: Despite the increasing prevalence of smartphone use while walking, few studies have comprehensively investigated head and neck posture in real-world settings. This study employed a single-blind observation of smartphone users walking in public areas of Taipei, Taiwan, to examine head and neck movements, with a particular focus on the effects of gender and hand-operation type. Methods: We conducted observations of 120 smartphone users (60 males and 60 females), recording neck flexion (NF), head flexion (HF), gaze angle (GA), and viewing distance (VD) in the sagittal plane during walking. The analysis included four combinations of gender and smartphone hand operation (one-handed and two-handed use). Results: Significant gender differences were found in NF (p < 0.001), GA (p < 0.01), and VD (p < 0.01), with males exhibiting greater NF, GA, and VD than females. HF was similar between genders, but males’ larger NF suggested a more pronounced forward head posture, potentially increasing neck and shoulder strain. Hand operations also significantly affected VD (p < 0.001). Most users displayed a GA exceeding 60°, possibly an involuntary adjustment for better visibility of the walking path, potentially increasing eyestrain. Conclusions: Previous studies have primarily simulated smartphone use while walking in controlled environments, such as on treadmills or in laboratories. In contrast, our single-blind field study highlights the real-world risks associated with smartphone use during walking, including neck and shoulder strain and eyestrain, with notable differences observed between genders.